1993
DOI: 10.1111/j.1365-2265.1993.tb00519.x
|View full text |Cite
|
Sign up to set email alerts
|

The hypothalamo‐pituitary‐adrenal axis across the normal menstrual cycle and in polycystic ovary syndrome

Abstract: The hyperandrogenism of polycystic ovary syndrome cannot be explained by enhanced ACTH secretion. Normal circulating cortisol levels, yet elevated dehydroepiandrosterone sulphate levels, suggests that polycystic ovary syndrome is yet another example of discrepant adrenal glucocorticoid and androgen secretion, and provides further evidence for a putative adrenal androgen stimulating factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 31 publications
1
13
1
1
Order By: Relevance
“…Stewart et al (19) suggested that enhanced clearance of cortisol caused by increased 5␣-reductase activity could lead to a counterregulatory activation of the HPA axis and thus to enhanced adrenal androgen generation. However, they failed to demonstrate an increase in ACTH secretion or pulsatility in a follow-up study (25).…”
Section: Discussionmentioning
confidence: 94%
“…Stewart et al (19) suggested that enhanced clearance of cortisol caused by increased 5␣-reductase activity could lead to a counterregulatory activation of the HPA axis and thus to enhanced adrenal androgen generation. However, they failed to demonstrate an increase in ACTH secretion or pulsatility in a follow-up study (25).…”
Section: Discussionmentioning
confidence: 94%
“…The total 24-h F [55], free F [56], the sensitivity or responsivity of F to ACTH stimulation [48], or the F or ACTH levels across the menstrual cycle [57] are relatively normal in PCOS while the 24-h urine free F concentration appear to be increased [58]. This discrepancy between serum measures of F and the urinary excretion of F suggests that the metabolism of this steroid may be accelerated in PCOS.…”
Section: C) Abnormalities In the Metabolism Of Cortisol In Pcosmentioning
confidence: 99%
“…Nonetheless, if the HPA axis were subtly, but chronically, overactive, it could result in subclinical hypertrophy and/or hyperplasia of the zonae reticularis/fasciculata, with a consequent overresponse to ACTH stimulation. In support of this hypothesis, Stewart et al reported that the ACTH pulse frequency was lower in seven women with PCOS than in nine controls (3.6 Ϯ 0.4 vs. 5.9 Ϯ 0.6 pulses/12 h; P Ͻ 0.05), with no change in mean pulse amplitude or level, suggesting some blunting of the HPA axis (8). Nonetheless, changes in the HPA axis may actually reflect primary alterations in adrenocortical biosynthesis, e.g.…”
Section: Fig 4 the Mean (ϯSd) Amentioning
confidence: 92%
“…a gland that intrinsically overresponds to ACTH may result in the compensatory reduction or blunting of the hypothalamic-pituitary response. Hence, although very subtle and minimal defects in hypothalamic-pituitary function may be present in PCOS patients with DHS excess (8,20), it is unlikely that we have missed a significant defect.…”
Section: Fig 4 the Mean (ϯSd) Amentioning
confidence: 99%